Biogas cleanup technology and reuse as fuel - Keen, Alex R. (Knovel, 2010)
Sustainable Energy & Development. New advances in H₂S control technologies from ALTECH Technology System Inc make it possible to remove H₂S from biogas during processing so it can be used as clean fuel.
Title from title page (viewed Sept. 3, 2010).
Keywords: Biogas.; Hydrogen sulfide.; Renewable energy sources.; elektronické knihy; electronic books